Sustainability drivers and inhibitors for the health system performance improvement projects in selected health facilities in Kenya: a qualitative study. Issue 7 (2nd July 2021) - Chelagat, Tecla; Kokwaro, Gilbert; Onyango, Joseph; Rice, Jim
Abstract : Objectives: To investigate the health managers perceived sustainability status of the health facilities institutional improvement projects and their experiences on factors that facilitated or constrained their maintenance, with intentions of informing relevant strategies or policies in Kenya's health sector. Methods: A qualitative study, nested within a quasi-experimental study. Thirty-three project-teams of health managers were purposively selected and interviewed based on their project implementation success rates post-training. The managers had previously undergone a 9-month leadership training, complimented with facility-based team coaching around the chosen projects. The training was funded by the US Agency for International Development; however, the implementation of the projects was based on how the participants could innovatively use the existing resource to create a positive change. The projects were housed within 20 public, 9 faith-based and 4 private health facilities in 19 counties in Kenya. The interviews explored the manager's experiences in sustaining the successfully implemented projects within the (24–60 months post-training period). We asked managers to describe factors they perceived enabled or hindered the sustainability of the successfully implemented institutional improvement project. The digitally audio-recorded interviews were transcribed verbatim. Data on barriers and enablers were thematically analysed. Results: Twenty-nine out of the 33 successfully implemented projects reported sustainability within periods ranging from 24 to 60 months post-training. Seven themes related to drivers of sustainability emerged, namely; programme design, stakeholder's buy-in, board members, communication, coaching, presence of change champion, devolution and political good-will. Four sustainability inhibitors identified were: human resources constraints, policy implementation, misalignment of projects with daily operations, devolution and political interference. Conclusions: The sustainability of institutional improvement strategies such as projects implemented post-leadership training in public and private health facilities depends on the quality of board members, communication management and institutionalisation of coaching culture. These findings are pertinent for planning and implementing similar health systems strengthening intervention in low-income countries.